"Crystallographic" holes: new insights for a beneficial structural feature for photocatalytic applications. Issue 13 (11th March 2015) - Vajda, Krisztina; Kása, Zsolt; Dombi, András; Németh, Zoltán; Kovács, Gábor; Danciu, Virginia; Radu, Teodora; Ghica, Corneliu; Baia, Lucian; Hernádi, Klára; Pap, Zsolt
Abstract : The "crystallographic" holes obtained by simple hydrothermal crystallization/calcination can enhance the photocatalytic activity of TiO2 microcrystals with exposed 001 facets. Abstract : One of the most fundamental aspects of the heterogeneous catalysis field is the manipulation of the catalysts' activity. In photocatalysis this is carried out by maximizing the right crystal plane of a semiconductor oxide. Until now, most of the papers have achieved this by a combination of different oxides, with noble metals and sometimes with carbon nanomaterials. In this work MWCNTs (multiwalled carbon nanotubes) were applied as "crystallization promoters" in a very simple, safe, one-step hydrothermal method. By this method TiO2 nano/micro crystals with exposed 001 facets were obtained in the first step. The next episode in the crystal manipulation "saga" was the modification of the (001) crystallographic plane's structure by creating ordered/own faceted "crystallographic holes". These elements are capable of further enhancing the obtained activity of titania microcrystals to a higher extent, as shown by the UV driven photocatalytic phenol degradation experiments. The appearance of the holes was "provoked" by simple calcination and their presence and influence were demonstrated by XPS and HRTEM.